International Aid for Development? An Overview Japanese ODA to Indonesia - Bahri, M Mossadeq (UI Scholars Hub, 2004)
This Paper examines at a general level the utility of Japanese Official Development Assistance (ODA) program, where it is dispatched to, and its consequences to the recipient countries. In this paper special attention is given to Japanese ODA to Indonesia. In this paper I argue that the Japanese government has pursued, and still does pursue, aid relations with its neighbour seeking foremost political and economic benefit for Japan. Benefits for other are a secondary concern.